2016
DOI: 10.1108/ijoem-04-2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

Firm and country specific determinants of capital structure in Sub Saharan Africa

Abstract: Purpose The purpose of this paper is to examine the effects of firm- and country-specific factors on the dynamics of capital structure for a new data set of firms in Sub-Saharan Africa. Design/methodology/approach Panel data estimation techniques are carried out on a set of 412 firms from 12 countries within Sub-Saharan Africa. Findings The results show that firm- and country-specific factors play an important role in the choice of debt for firms in Sub-Saharan Africa. First, firm profitability is the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 80 publications
8
28
0
2
Order By: Relevance
“…Therefore, bank leverage ratio is negatively associated with profitability of banks and similar pattern is also observed in our study. These results are coherent with pecking order theory of capital structure which exhibits negative association between profitability and level of debt (Chipeta & Deressa, 2016). In our sample of banks, tangibility is negatively related with bank leverage in CBs, while insignificant in sample of IBs.…”
Section: Results Of Dynamic Modelingsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, bank leverage ratio is negatively associated with profitability of banks and similar pattern is also observed in our study. These results are coherent with pecking order theory of capital structure which exhibits negative association between profitability and level of debt (Chipeta & Deressa, 2016). In our sample of banks, tangibility is negatively related with bank leverage in CBs, while insignificant in sample of IBs.…”
Section: Results Of Dynamic Modelingsupporting
confidence: 90%
“…However, impact of firm level factors exhibit under the umbrella of institutional factors as well as macro environmental factors embodying sensible differences in intensity and magnitude of their impact. As in the work of Chipeta and Deressa (2016), impact of profitability on leverage increases in countries with least developed stock and banking markets. This area is eye catching in research on capital structure because literature on financial decision making somehow empirically reports industry or sectoral impact on financial decisions of firms operating in the same industry (Antoniou, Guney, & Paudyal, 2008;MacKay & Phillips, 2005).…”
Section: Bank Leverage and Environmental Outlookmentioning
confidence: 86%
“…Several studies confirmed that assets tangibility has a positive relationship with leverage level which is in line with the Trade-off theory (Berkman, Iskenderoglu, Karadeniz, & Ayyildiz, 2016;Deesomsak, Paudyal, & Pescetto, 2004;Dhingra & Dev, 2016;Hussain et al, 2015;Md-Yusuf, Mohammad Yunus, & Md Supaat, 2013;Sabir & Malik, 2012;Vo, 2017). Matias and Serrasqueiro (2017), Vo (2017), Chipeta and Deressa (2016), Oino and Ukaegbu (2015), Proença, Laureano, and Laureano (2014), Taddese Lemma and Negash (2013), Ting and Lean (2011) showed evidence that assets tangibility has a positive relationship with long-term debt as posited by Trade-off theory, and it has a negative relationship with short-term debt as posited by Pecking Order theory. Thus, it suggests that most of the firms use tangible assets as collateral to issue long-term debt, hence being less dependent on short-term debt.…”
Section: Tangibilitysupporting
confidence: 63%
“…This is because the use of retained earnings can avoid the issuance cost of debt and equity. According to Chipeta and Deressa (2016), in developing countries, the capital markets are not well-developed. It is supported by Vo (2017), Bekaert and Harvey (2017) that firms in developing countries heavily rely on banks as a major source of financing.…”
Section: Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation